PENINGKATAN PERKEMBANGAN MOTORIK HALUS MELALUI KEGIATAN MERONCE PADA ANAK KELOMPOK A DI TK NEGERI SIGERONGAN - Febrianti, Anis; Suarta, I Nyoman; Astawa, I Made Swasa; Rahayu, Dwi Istati (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2018)
This type of research is a development research with 3 stages of development, each development consisting of planning, implementation, observation and reflection. The subjects of this study were children aged 4-5 years in group A totaling 10 people. Data collection in this study used observation and documentation methods. The data that has been collected was then analyzed descriptively qualitatively. The results of the study showed that in the development stage I, an average result of 59.25% was obtained, while in the development stage II it began to increase with an average value of increasing children's fine motor development reaching 73.37% developing quite well and in the development stage III the average value of increasing children's fine motor development increased to 85.87% with the criteria developing according to expectations. Based on the results of the study, it can be concluded that the development of fine motor skills through stringing activities in children aged 4-5 years at Sigerongan State Kindergarten. Stringing activities can improve the development of fine motor skills in children in group A at Sigerongan State Kindergarten in the 2017/2018 academic year.